2014
DOI: 10.3389/fnint.2014.00064
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal oscillations form parietal/frontal networks during contour integration

Abstract: The ability to integrate visual features into a global coherent percept that can be further categorized and manipulated are fundamental abilities of the neural system. While the processing of visual information involves activation of early visual cortices, the recruitment of parietal and frontal cortices has been shown to be crucial for perceptual processes. Yet is it not clear how both cortical and long-range oscillatory activity leads to the integration of visual features into a coherent percept. Here, we wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 76 publications
(154 reference statements)
1
15
1
Order By: Relevance
“…In addition to disturbances in visual cortex, however, the one prior fMRI study of SCZ demonstrated reduced prefrontal cortex and parietal lobe processing in patients. These data are consistent with recent findings indicating that in addition to visual cortex, frontal-parietal connectivity and other mechanisms supporting higher-level top-down control are involved in contour integration and object processing (Castellano, Plochl, Vicente, & Pipa, 2014; Hanslmayr, Volberg, Wimber, Dalal, & Greenlee, 2013; Li, Piech, & Gilbert, 2008; Sun et al, 2012; Volberg, Wutz, & Greenlee, 2013). The CI data reviewed above are supported by data from studies of perceptual closure, where subjects view fragmented line drawings of familiar objects.…”
Section: 0 Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition to disturbances in visual cortex, however, the one prior fMRI study of SCZ demonstrated reduced prefrontal cortex and parietal lobe processing in patients. These data are consistent with recent findings indicating that in addition to visual cortex, frontal-parietal connectivity and other mechanisms supporting higher-level top-down control are involved in contour integration and object processing (Castellano, Plochl, Vicente, & Pipa, 2014; Hanslmayr, Volberg, Wimber, Dalal, & Greenlee, 2013; Li, Piech, & Gilbert, 2008; Sun et al, 2012; Volberg, Wutz, & Greenlee, 2013). The CI data reviewed above are supported by data from studies of perceptual closure, where subjects view fragmented line drawings of familiar objects.…”
Section: 0 Introductionsupporting
confidence: 93%
“…Parietal ROIs included: 1) the superior parietal lobules, which are involved in the distribution of visual-spatial attention and the binding of visual features (Robertson, 2003), and which were associated with reduced CI in schizophrenia in our past study (Silverstein et al, 2009); and 2) the angular gyrus, which is involved in integrating visual information with the verbal and spatial concepts of left and right during left-right discrimination (Hirnstein, Bayer, Ellison, & Hausmann, 2011; Seghier, 2013), a process essential for accurate JOVI performance. Frontal ROIs were the middle and inferior frontal gyri (including the pars triangularis and pars operculum regions), which are involved in perceptual organization and perceptual decision making (Ploran et al, 2007; Sun et al, 2012), as was recently shown using a CI task similar to the JOVI in healthy subjects in a study of neuronal oscillations (Castellano et al, 2014). …”
Section: 0 Methodsmentioning
confidence: 99%
“…Sutoyo and Srinivasan (2009) have elicited enhanced responses to conscious binding of congruent information from complementary hemi-fields into a coherent percept. Although their findings cannot be directly linked to the present results, they strongly imply that early beta synchronization is sensitive to the integration of visual information from the two hemi-fields (Mima et al, 2001;Phillips and Takeda, 2009;Phillips et al, 2012;Busch et al, 2004;Castellano et al, 2014). As indicated by the stimulus-type effect in controls, binding congruent information into a coherent fullfield percept is associated with stronger beta synchronization between right parietal and frontal regions, which, however, was specifically impaired in the N+ group (Fig.…”
Section: Fronto-parietal Beta Synchronization During Visual Processingcontrasting
confidence: 60%
“…Hipp et al (2011) have identified large scale beta synchronization in a distinctive network of frontal, parietal and extrastriate visual areas in relation to visual perceptual organization. Fronto-parietal synchrony in the beta band also has been associated with visual search (Buschman and Miller, 2007), integration of visual information and perceptual grouping (Srinivasan et al, 1999;Phillips and Takeda, 2009;Phillips et al, 2012;Volberg and Greenlee, 2014;Castellano et al, 2014), visual attention (Gross et al, 2004;Marois et al, 2000;Wróbel, 2000), and visual object recognition (Sehatpour et al, 2008;Castellano et al, 2014). These previous studies, however, point to the existence of ongoing fronto-parietal beta synchronization that modulates brain responses to visual input (Gross et al, 2004;Liang et al 2002;Hipp et al, 2011), or beta synchrony at later stages (150-300 ms) of visual stimulus processing (Phillips et al, 2012;Sehatpour et al, 2008;Dehaene and Changeux, 2011).…”
Section: Fronto-parietal Beta Synchronization During Visual Processingmentioning
confidence: 98%
“…For example, it has been shown that detection of the figure involves synchronization at gamma frequencies within early visual regions, whereas categorization of the orientation of the egg-shaped figure formed by the contour involves synchronization at beta frequencies across a network that includes frontal and parietal regions (Castellano et al, 2014).…”
Section: Gestalt Groupingmentioning
confidence: 99%